2023
DOI: 10.1186/s13287-023-03476-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mesenchymal stem cell survival and homing capability to improve cell engraftment efficacy for liver diseases

Shaoxiong Yu,
Saihua Yu,
Haiyan Liu
et al.

Abstract: Although mesenchymal stem cell (MSC) transplantation provides an alternative strategy for end-stage liver disease (ESLD), further widespread application of MSC therapy is limited owing to low cell engraftment efficiency. Improving cell engraftment efficiency plays a critical role in enhancing MSC therapy for liver diseases. In this review, we summarize the current status and challenges of MSC transplantation for ESLD. We also outline the complicated cell-homing process and highlight how low cell engraftment ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 133 publications
1
4
0
Order By: Relevance
“…Most transplanted cells had disappeared, which limits the number of transplanted SLCs differentiated into LCs. In line with a previous study, mesenchymal stem cells display poor survival and engraftment rates in vivo, and their short lifespan could be explained by the stresses encountered after local transplantation, such as nutrient deprivation and proinflammatory cytokines 45,46 . Moreover, a previous study reported that in vivo differentiated stem cells elicit enhanced immunogenicity, thereby increasing their chance for rejection 47,48 .…”
Section: Discussionsupporting
confidence: 84%
“…Most transplanted cells had disappeared, which limits the number of transplanted SLCs differentiated into LCs. In line with a previous study, mesenchymal stem cells display poor survival and engraftment rates in vivo, and their short lifespan could be explained by the stresses encountered after local transplantation, such as nutrient deprivation and proinflammatory cytokines 45,46 . Moreover, a previous study reported that in vivo differentiated stem cells elicit enhanced immunogenicity, thereby increasing their chance for rejection 47,48 .…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the survival and homing capabilities of MSCs are compromised under challenging conditions such as low oxygen tension, fluid pressure stress, and interactions with whole blood components postinjection. This process is further complicated by hypoxia, oxidative stress, and inflammation at targeted sites[ 68 ]. Alarmingly, significant concerns regarding potential risks, including tumorigenesis and adverse immune reactions must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we summarize the current status of mesenchymal stem cell therapy and the challenges in translational application of clinical therapy. Various biological, biochemical and biophysical factors affect the survival and homing ability of MSCs through the interplay between cells, extracellular matrix and bioactive factors in vitro and in vivo ( 177 ). Therefore, by regulating the above factors to reduce cell damage, improve the survival rate of MSCs, increase the homing ability of MSCs and improve the efficiency of MSCs implantation.…”
Section: Discussionmentioning
confidence: 99%